Utility of Histologic and Histochemical Screening for 16S Ribosomal RNA Gene Sequencing of Formalin-Fixed, Paraffin-Embedded Tissue for Bacterial Endocarditis. Issue 4 (7th June 2019) - Solomon, Isaac H; Lin, Chieyu; Horback, Katharine L; Kanjilal, Sanjat; Rojas-Rudilla, Vanesa; Brigl, Manfred; Laga, Alvaro C; Lindeman, Neal I; Padera, Robert F
Abstract: Objectives: 16S ribosomal RNA (rRNA) sequencing is a powerful but expensive tool for the identification of bacteria in culture-negative endocarditis. Histologic criteria to screen formalin-fixed, paraffin-embedded (FFPE) specimens for testing are evaluated. Methods: Sixty-eight cases of infective endocarditis and controls were histologically reviewed and analyzed by 16S rRNA gene sequencing. Results: Sequencing identified a specific pathogenic organism in 33 (49%) of 68 cases with acute inflammation and in 0 of 10 controls ( P = .004). Visualization of organisms by Gram or Grocott methenamine silver stains had the strongest association with positive sequencing, while antibiotic treatment effect and acid decalcification decreased sensitivity. Molecular identifications were concordant with blood culture results in 90% of the cases, and a positive sequencing result was obtained in approximately half of the cases with negative valve cultures. Conclusions: Histologic screening criteria are extremely helpful for identifying cases likely to be positive by molecular testing and can provide significant cost savings in filtering out low-yield specimens.